Validation of growth enhancing, immunostimulatory and disease resistance properties of Achyranthes aspera in Labeo rohita fry in pond conditions. Issue 2 (February 2019) - Kumar, Neelesh; Sharma, JaiGopal; Singh, Samar Pal; Singh, Amarjeet; Hari Krishna, V.; Chakrabarti, Rina
Abstract: The immunostimulatory and disease resistance properties of herb Achyranthes aspera L. (Amaranthaceae) were evaluated in rohu Labeo rohita in pond. Rohu fry (1.9 ± 0.08 g) were cultured in hapas (25 hapa −1 ) set inside a pond and were fed with two experimental diets containing 0.5% seeds (D1) and leaves (D2) of A. aspera and control diet (D3). Fish were challenged with Aeromonas hydrophila after 80 days. The cumulative mortality rate of fish was significantly ( P < 0.05) higher in D3 (28–48%) compared to others. Average weight was significantly ( P < 0.05) higher in D1 (6.5–12.5%) compared to other treatments. Myeloperoxidase and nitric oxide synthase levels were significantly ( P < 0.05) higher in D1 and D2 compared to D3. Thiobarbituric acid reactive substances and carbonyl protein levels were significantly ( P < 0.05) lower in hepatopancreas and kidney of D1 compared to others. In hepatopancreas, the expressions of lysozyme C, loysozyme G, TNF-α, IL-10 and IL-1β were significantly ( P < 0.05) higher in D1 compared to others. This treatment was followed by D2. In kidney, lysozyme G and TNF-α levels were significantly ( P < 0.05) higher in D1 and D2 compared to D3. Whereas, IL-10 and IL-1β were significantly ( P < 0.05) down-regulated and up-regulated, respectively in kidney of D2. There was up-regulation ( P < 0.05) of TLR-4 in hepatopancreas and kidney of D1 and D2 diets fed rohu, respectively compared to others.